Defect list at semi-D housing project / Muhammad Izzat Farhan Mustapa - Mustapa, Muhammad Izzat Farhan (Universiti Teknologi MARA, Perak, 2019)
As the modem society continued to strived, day by day a piece of land is contributed with the purpose of building construction. Looking it in positive perspective it could boost the society to move forward in a faster pace but the one thing that society is forgetting is that they tend to focus more on the quantities of the building rather than its quality. This is due to the human nature to be clouded with greed. Thus, making the building more vulnerable to defect.